Peripheral giant cell granuloma - Adlakha V; Chandna P; Rehani U; Rana V; Malik P (Wolters Kluwer Medknow Publications, 2010)
Peripheral giant cell granuloma is a benign reactive lesion of gingiva. It manifests as a firm, soft, bright nodule or as a sessile or pedunculate mass. This article reports the management of peripheral giant cell granuloma in a 12-year-old boy by surgical excision.